Do not ignore the Participation of smoking men in caring for their pregnant wives from exposure to Secondhand Smoke - Zohreh Karimiankakolaki (Journal of Social Behavior and Community Health, 2022)
Men's smoking is a source of exposure to tobacco smoke, which is linked to the amount of cotinine in pregnant women (Taylor et al., 2014). The rate of exposure to secondhand smoke in pregnant women in Iran was 23.1% (MazloomyMahmoodabad et al., 2019). Addressing SHS exposure in pregnancy in low-